Prognostic value of metastatic lymph node ratio in patients with gastric carcinoma - Duraker, Nüvit (Cerrahpaşa Medical Journal, 2019)
Objectives: In order to classify metastatic lymph nodes according to TNM classification in gastric carcinoma, at least 16 lymph nodes have to be excised. In patients with less than 16 lymph nodes removed, nodal classification may be accomplished with respect to the ratio of the number of metastatic lymph nodes to the number of lymph nodes removed (lymph node ratio). In this study, the prognostic significance of lymph node ratio in gastric carcinoma patients who underwent D1 lymph node dissection was investigated. Methods: One hundred seventy seven node positive gastric carcinoma patients who underwent potentially curative resection were included in the study. Data was collected prospectively. Patients were divided as Group 1 (number of removed lymph nodes less than 16, 87 patients) and Group 2 (number of removed lymph nodes 16 and higher, 90 patients). A number of threshold values with regard to lymph node ratio which separated the patients into various subgroups with similar patient numbers and significantly different survival rates were investigated. Results: In Group 1, patients with a lymph node ratio ≤0.40 had a significantly better 5-year overall survival rate (44.4%) than those with this ratio >0.40 (11.8%) (p<0.0001), and the patients were also significantly separated into three subgroups according to 0.35 and 0.70 ratio values. These two patient groupings had independent prognostic significance in multivariate Cox analysis (p= 0.001 for both). In Group 2, 5-year overall survival for the patients with lymph node ratio ≤0.30 (41.7%) was significantly better than those with this ratio >0.30 (9.1%) (p=0.0026), and threshold values that separated the patients into three groups as near to the significance limit were 0.40 and 0.80. These two patient groupings had borderline significance in Cox analysis (p=0.050 and p=0.055, respectively). Conclusion: In gastric carcinoma patients, lymph node ratio may be utilized for determination of prognostic node groups in patients with both less than 16 lymph nodes removed and 16 and higher lymph nodes removed.